Algorithmic approach to the lymphatic leak after vascular reconstruction: a systematic review - Nicksic, Peter John; Condit, Kevin Michael; Nayar, Harry Siva; Michelotti, Brett Foster (Archives of Plastic Surgery, 2021)
Background To date, there are no consensus guidelines for management of lymphatic leak in groin vascular reconstruction patients. The goal of this study is to review the relevant literature to determine alternatives for treatment and to design an evidence-based algorithm to minimize cost and morbidity and maximize efficacy.Methods A systematic review of the literature was conducted per Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) protocol. Two independent reviewers applied agreed-upon inclusion and exclusion criteria to eligible records. Studies that included patients who underwent groin dissection for oncologic diagnoses and level 5 data were excluded. Interventions were then categorized by efficacy using predetermined criteria.Results Our search yielded 333 records, of which eight studies were included. In four studies, the success of lymphatic ligation ranged from 75% to 100%, with average days to resolution ranging from 0 to 9. Conservative management in the form of elevation, compression, and bedrest may prolong time to resolution of lymphatic leak (14–24 days) and therefore cost.Conclusions The majority of patients should be offered early operative intervention in the form of lymphatic ligation with or without a primary muscle flap. If the patient is not an operative candidate, a trial of conservative management should be attempted before other nonsurgical interventions.
Keywords: Lymph; Lymphorrhea; Algorithms; Blood vessel prosthesis